Muslim Scholars' Perceptions of Indonesia's New Halal Logo: A Consumer Behavior Perspective - Hasan, Jamaludin; Jamal, Ridwan; Samad, Telsy Fratama Dewi; Luntajo, Moh. Muzwir R. (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Manado, 2025)
The introduction of a new halal logo in Indonesia by the Halal Product Assurance Agency (BPJPH) in 2022 has triggered wide-ranging public responses, particularly from Muslim consumers and stakeholders. This study explores the perceptions of Islamic economics scholars regarding the new halal logo, analyzed through the lens of Muslim consumer behavior theory. Using a descriptive qualitative approach, data were collected through in-depth interviews with eight lecturers from the Faculty of Islamic Economics and Business at the State Institute for Islamic Studies (IAIN) Manado. The findings reveal that five out of eight participants expressed disapproval toward the new logo, citing its aesthetic complexity, lack of clear Islamic symbolism, and cultural partiality—factors they argue diminish recognition and trust among Muslim consumers. Conversely, three respondents supported the redesign, viewing it as a cultural representation of Indonesian identity and a fresh approach to halal branding. The study also uncovers critical reflections on the shift in halal certification authority from the Indonesian Ulema Council (MUI) to BPJPH. This research contributes to the growing body of literature on halal consumer perception and suggests that policy efforts must be accompanied by public education to ensure acceptance and functionality of halal symbols. The results underscore the importance of religious-cultural alignment and visual clarity in halal certification communication strategies.